(untitled) (Jurnal Studi Komunikasi, 2022)
YouTube challenges the media monopoly by providing spaces for everyone to produce including the cultural industry products like podcasts. Deddy Corbuzier took advantage of this opportunity by opening a channel on YouTube. At first, Deddy criticised the ‘garbage’ broadcast on television, but then he invited Dinar Candy and managed to become a top view the worst video he has ever made. This study looks at the commodification of two Deddy Corbuzier’s YouTube content with Dinar Candy and Siti Fadilah Supari and sees it from Adorno’s critical point of view of the cultural industry. This research uses multimodality analysis and critical discourse analysis. The result is Deddy Corbuzier, who was first known as a YouTuber with critical content and used YouTube to resist media monopoly. However, he compromised his integrity, followed capitalism’s flow, and created content for profit by repeating his success for popular and uncritical videos.